Analysis on Hover Control Performance of T- and Cross-Shaped Tail Fin of X-Wing Single-Bar Biplane Flapping Wing - Pingxia Zhang; Junru Zhu; Yongqiang Zhu (Journal of Robotics)
The current flapping wing adopts T-shaped or cross-shaped tail fin to adjust its flight posture. However, how the tail fin will affect the hover control is not very clear. So, the effects of the two types of tail on flight will be analyzed and compared by actual flight tests in this paper. Firstly, we proposed a new X-wing single-bar biplane flapping-wing mechanism with two pairs of wings. Thereafter, the overall structure, gearbox structure, tail, frame, and control system of the flapping wing were designed and analyzed. Secondly, the control mechanism of hover is analyzed to describe the effect of two-tail fin on posture control. Thirdly, the Beetle was used as the control unit to achieve a controllable flight of flapping wing. The MPU6050 electronic gyroscope was used to monitor the drone’s posture in real time, and the Bluetooth BLE4.0 wireless communication module was used to receive remote control instructions. At last, to verify the flight effect, two actual flapping wings were fabricated and flight experiments were conducted. The experiments show that the cross-shaped tail fin has a better controllable performance than the T-shaped tail fin. The flapping wing has a high lift-to-mass ratio and good maneuverability. The designed control system can achieve the controllable flight of the flapping wing.